Microstructural Evolution and Mechanical Properties of an Interstitial-Free Steel Processed by Equal-Channel Angular Pressing - Verma, Deepa (IIT (BHU) varanasi, 2016)
Grain refinement in a polycrystalline material to micron level is known for its beneficial effects of enhancing both strength and ductility. Severe plastic deformation (SPD) methods specially equal-channel angular pressing (ECAP) can be adopted for refinement to ultrafine level where grain size of the order of ~200-300 nm can be achieved, which is an order of magnitude higher than that can be obtained by thermomechanical treatment (TMT). Ultra high strength, ductility and high toughness are required along with reduce mass, improved safety and performance in transportation equipments. ECAP of alloys enhances yield strength to grain refinement to ultra high range due to ultrafine level (<1µm) but ductility gets reduced comparison to their coarse grained counterpart due to limited dislocation activity. The solutions to these problems are not yet found because of which, the applications of UFG materials are delayed. Grain refinement of low carbon steel suggests that microstructure of bimodal grain size distribution where majority of grains are in ultrafine range carrying high stress or load and small fraction of grains in 1-10 µm range restore ductility can be achieved in metals and alloys of mixed microstructure. Wang et al. have shown that ductility in electrical grade copper can be regained while retaining strength to about six times that of coarse grained counterpart by effecting bimodal grain size distribution through cryorolling followed by short annealing above secondary recrystallization temperature. Therefore, the solution to the problem is to optimize strength and ductility by producing mixture of ultrafine grains and micron sized grains in the microstructure. Such a microstructure can be achieved by combining optimized ECAP parameters with post ECAP deformation and annealing. Interstitial free (IF) steels are known for their high formability but their low strength acts as a detriment to their wider applications. There is a need to improve the strength of the material with maintaining ductility. Therefore, the present investigation is focused on the refinement of interstitial-free steel to ultrafine-grain level by ECAP to get ultra high strength and post deformation of UFG IF steel by cold rolling and cryorolling to refine the material further. One of the other major objectives is to get bimodal/multimodal grain size distribution in IF steel processed by ECAP and post ECAP deformation followed by flash annealing. Structure-property correlations are to be established
Keywords: Microstructural Evolution; Mechanical Properties of an Interstitial-Free Steel Processed; Equal-Channel Angular Pressing